GEOINFORMATION PORTAL AS THE COMPONENT OF THE UNIFORM GEOINFORMATION ENVIRONMENT OF THE ARMED FORCES OF UKRAINE - Lytvynenko, N.; Korenets, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The modern views on armed struggle, their impact on the tactics of using troops (forces) in the war with the russian federation, new asymmetric threats to Ukraine’s national security, as well as reforming the Armed Forces of Ukraine require a review of information requirements. perform geoinformation support of the Armed Forces of Ukraine. The importance and necessity of the implementing and using of geographic information systems for military purposes is due to the general increase in the requirements of troops (forces) to the efficiency, completeness and quality of information support of the management process. The armed aggression of the russian federation against Ukraine creates new challenges to the information security of the state and leads to the revision of the requirements for information support in general and for geoinformation support in particular. It’s determined that the foundation of the Unified Geoinformation Environment of the Armed Forces should be service-oriented architecture (SOA) of distributed geodatabases, that provides a common platform for all entities and users to access the resources of Unified Automated Control System of the Armed Forces of Ukraine. The Unified Geoinformation Environment (UGIE) of the Armed Forces of Ukraine should be formed as an combination (network) of interconnected geoportals, the purpose of that is to consolidate information on available in the Unified Automated Control System of the Armed Forces spatial data. user entry points into this environment. The UGIE of the Armed Forces of Ukraine should provide access to data stored in the system of distributed geodatabases. The format and use of services should be based on the use of national, international and military standards, that are the only agreed and approved set of standards for data, interfaces and computer programs developed on the basis of service-oriented architecture.